Analisis Perbedaan Tarif Rumah Sakit dan Tarif INA-CBG’s Pelayanan Rawat Jalan di RSUD Budhi Asih Jakarta Tahun 2015 - Dumaris, Hotma (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2016)
There is a fundamental change of hospital’s payment system in Indonesia since the Indonesian National Health Insurance was implemented (January 2014). The former retrospective payment system was changed into prospective payment system with Indonesia Case Base Groups (INA-CBG) as expense base. This change forced hospital to propose a new efforts to adjust the rate difference between the previous hospital based-tariff system and the latter INA-CBG-based-tariff system in order to assure the health service quality. This study aims to find out hospital’s efforts to adjust the tariff difference between the hospital-based- tariff system and INA-CBG-based-tariff-system.This is a quantitative as well as qualitative research. There were 2384 cases analyzed, with 645 cases (27.1%) with positive tariff balance and 1739 cases (72.9%) with negative tariff balance. Tariff differences was Rp. 135.871.977 (27.5% of the total hospital tarif). Average hospital tariff was Rp. 221.683, while the average INA CBG’s tariff was Rp. 278.676 and average difference was Rp 56.993. Hospital claim for chronic disease, which was not included in INA-CBG’s list, increased the positive balance to Rp. 187.208.274 (35,42% of hospital total tariff). Medication became the biggest part of the hospital cost (37.4%). The hospital’s management had worked efficiently to control the cost and assure the quality. Cost-efficiency-efforts as well as good remuneration system had been implemented from planning to evaluation. Hospital had to arrange and implement the clinical pathway as a standardization as well as quality control.